2022
DOI: 10.3390/cells11050795
|View full text |Cite
|
Sign up to set email alerts
|

PYL1- and PYL8-like ABA Receptors of Nicotiana benthamiana Play a Key Role in ABA Response in Seed and Vegetative Tissue

Abstract: To face the challenges of climate change and sustainable food production, it is essential to develop crop genome editing techniques to pinpoint key genes involved in abiotic stress signaling. The identification of those prevailing abscisic acid (ABA) receptors that mediate plant-environment interactions is quite challenging in polyploid plants because of the high number of genes in the PYR/PYL/RCAR ABA receptor family. Nicotiana benthamiana is a biotechnological crop amenable to genome editing, and given the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Specifically, ABA receptor subfamilies PYL1/2-like and PYL8/9-like were downregulated and upregulated in high producers, respectively ( Supplementary Table S4 ). PYL8/9-like upregulation could indicate higher sensitivity of SxP high producers to growth-inhibiting effects of ABA, since the pyl8a , pyl8b , and pyl8c mutants are insensitive to ABA for growth and development inhibition in shoots ( Pizzio et al., 2022 ). Downstream ABA signalling was activated as well, as evidenced by upregulation of genes with homology to ABA-responsive ABF2 and ABF3 transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, ABA receptor subfamilies PYL1/2-like and PYL8/9-like were downregulated and upregulated in high producers, respectively ( Supplementary Table S4 ). PYL8/9-like upregulation could indicate higher sensitivity of SxP high producers to growth-inhibiting effects of ABA, since the pyl8a , pyl8b , and pyl8c mutants are insensitive to ABA for growth and development inhibition in shoots ( Pizzio et al., 2022 ). Downstream ABA signalling was activated as well, as evidenced by upregulation of genes with homology to ABA-responsive ABF2 and ABF3 transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…The complete seedlings obtained from the in vitro culture of shoot tips and uninodal segments initiated the acclimatization process following the methodologies suggested by Dias et al [21] and Pizzio et al [63] with modifications. Briefly, the day before transplanting into soil, the seedlings (n=15) were treated with ABA solution at concentrations of 50 µM and 100 µM via spraying on adaxial and abaxial sides of leaves, whereas those mock treated served as the control group.…”
Section: Acclimatization To Ex Vitro Conditions and Aba Treatmentmentioning
confidence: 99%
“…These proteins perceive the hormone and form a ternary complex between ABA-PYL-PP2CA, triggering the signaling cascade and response. The PYL family is composed of several members, for instance 12 PYLs in palm [54], 14 PYLs in tomato [55], 12 PYLs in rice [56], 23 PYLs in N. benthamiana [57], 29 PYLs in tobacco [58], and 38 PYLs in wheat [59]. Recently, 20 PYLs were identified in quinoa (Figure 1) [60].…”
Section: Aba Perception and Signaling In Quinoamentioning
confidence: 99%
“…Recently, 20 PYLs were identified in quinoa (Figure 1) [60]. The phylogenetic classification of these 20 CqPYLs grouped the receptors in the three classical clades of ABA receptors: PYL8 subgroup (subfamily I), PYL4 subgroup (subfamily II), and PYL1 subgroup (subfamily III) [53,57,[61][62][63]. Furthermore, the expression profiles analysis of CqPYLs in 1-week-old seedlings showed that CqPYL8c-d and CqPYL4a-b were the most abundant ABA receptors, followed by CqPYL8a-b, CqPYL5a-b, CqPYL8e-f, and CqPYL1a-b [60].…”
Section: Aba Perception and Signaling In Quinoamentioning
confidence: 99%